Internet-Using Behavior of Thai Tourist for Travelling to Ubonratchathani Province - หิรัญเทศ, วันทิกา (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The research objectives were to; 1) study internet-using behavior of Thai tourist for travelling to Ubonratchathani Province and, 2) study relation between the personal factors and internet-using behavior of Thai tourist visiting to Ubonratchathani province. The samples of the research were 400 Thai tourists who travel to Ubonratchathani province, collected data by questionnaire. The statistics were analysis includes percentage, frequency, Chi-square test. The result of the research shows that; 1) most of Thai tourists have known information about the attractive tourism of Ubonratchathani from internet, searched information or shared experiences by Facebook or made reservation or payment by website of the hotel and; 2) relation between personal factors consisting of gender, age, education, and income per month and internet-using behavior of Thai tourist visiting to Ubonratchathani province are related statistically significantly at .05 level.